Restoring trade finance during a period of financial crisis: Stocktaking of recent initiatives - Marc Auboin (World Trade Organization (WTO), 2009)
The paper discusses the efforts deployed in 2008 and 2009 by various players, Governments, multilateral financial institutions, regional development banks, export credit agencies, to mobilize sufficient flows of trade finance to off-set some of the 'pull-back' by commercial institutions in the period of acute crisis that has characterized the financial sector in the past two years. Given that 80 to 90% of trade transactions involve some form of credit, insurance or guarantee, one can reasonably say that supply-side driven shortages of trade finance have a potential to inflict further damages to international trade. As an institution geared towards the balanced expansion of world trade, the WTO had been concerned with occurrences of market tightening throughout this period. While a number of public-institutions mobilized financial resources for trade finance in the fall of 2008, this has not been enough to bridge the gap between supply and demand of trade finance worldwide. As the market situation continued to deteriorate in the first quarter of 2009, G-20 leaders in London (April 2009) adopted a wider package for injecting additional liquidity and bringing public guarantees in support of 250 billion of trade transactions in 2009 and 2010. Ahead of the Pittsburgh Meetings, experts reported that more than the targeted amount had been mobilized. In the meantime, through the summer and the fall of 2009, the market situation seemed to have eased - although in many countries, access to trade finance by the smaller traders had become either significantly more expensive or had simply disappeared. One can expect the trade finance market to have its up and downs for some time, because lending for trade is a function of the general lending situation of commercial banks. The paper discusses longer-term initiatives aimed at improving the resilience of the trade finance market to short-term and longer-term shocks.
Keywords: F5; F13; L8; D72; 330; trade financing; cooperation with international financial institutions; coherence; G-20; financial crisis